Transnational climate change governance - Bulkeley, Harriet, 1972- (Cambridge : Cambridge University Press, 2014)
The world of climate politics is increasingly no longer confined to the activities of national governments and international negotiations. Critical to this transformation of the politics of climate change has been the emergence of new forms of transnational governance that cut across traditional state-based jurisdictions and operate across public and private divides. This book provides the first comprehensive, cutting-edge account of the world of transnational climate change governance. Co-authored by a team of the world's leading experts in the field and based on a survey of sixty case studies, the book traces the emergence, nature and consequences of this phenomenon, and assesses the implications for the field of global environmental politics. It will prove invaluable for researchers, graduate students and policy makers in climate change, political science, international relations, human geography, sociology and ecological economics.
Machine generated contents note: 1. Introducing transnational climate change governance; 2. Mapping the world of transnational climate change governance; 3. Theoretical perspectives on transnational governance; 4. Origins, agency and the forms of transnational climate change governance; 5. Constructing transnational climate change governance issues and producing governance spaces; 6. The uneven geography of transnational climate change governance; 7. Understanding authority and legitimacy in transnational climate change governance; 8. Making a difference? Tracing the effects and effectiveness of transnational climate change governance; 9. Conclusions - looking beyond transnational climate governance.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Climatic changes -- Government policy; Climatic changes -- International cooperation; Global environmental change -- Government policy; Global environmental change -- International cooperation